2020
DOI: 10.1007/s15010-020-01408-5
|View full text |Cite|
|
Sign up to set email alerts
|

Respiratory tract infection-related healthcare utilisation in children with Down’s syndrome

Abstract: Purpose Children with Down's syndrome (DS) are prone to respiratory tract infections (RTIs) due to anatomical variation, immune system immaturity and comorbidities. However, evidence on RTI-related healthcare utilisation, especially in primary care, is incomplete. In this retrospective cohort study, we use routinely collected primary and secondary care data to quantify RTI-related healthcare utilisation in children with DS and matched controls without DS. Methods Retrospective cohort study of 992 children with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…This finding has added significance because children with DS may be more at risk of antibiotic resistance given immune system immaturity and increased likelihood of receiving multiple antibiotic courses 27–30 . Despite this, children with DS are prescribed antibiotics for RTIs more frequently than healthy controls, at a rate of 42 per 100 person years for children with DS versus 19 per 100 person years for controls (adjusted RR, 2.26) 9 . The reasons for this are unclear and may be due to perceived benefits in other areas that have not been well‐studied.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This finding has added significance because children with DS may be more at risk of antibiotic resistance given immune system immaturity and increased likelihood of receiving multiple antibiotic courses 27–30 . Despite this, children with DS are prescribed antibiotics for RTIs more frequently than healthy controls, at a rate of 42 per 100 person years for children with DS versus 19 per 100 person years for controls (adjusted RR, 2.26) 9 . The reasons for this are unclear and may be due to perceived benefits in other areas that have not been well‐studied.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30] Despite this, children with DS are prescribed antibiotics for RTIs more frequently than healthy controls, at a rate of 42 per 100 person years for children with DS versus 19 per 100 person years for controls (adjusted RR, 2.26). 9 The reasons for this are unclear and may be due to perceived benefits in other areas that have not been well-studied. Previous studies have suggested that prescribing decisions are also related to parental expectation, uncertainty, and pressure from employers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations